2012
DOI: 10.1364/ao.51.002035
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of aerosol extinction coefficient profiles from Raman lidar data by inversion method

Abstract: We regard the problem of differentiation occurring in the retrieval of aerosol extinction coefficient profiles from inelastic Raman lidar signals by searching for a stable solution of the resulting Volterra integral equation. An algorithm based on a projection method and iterative regularization together with the L-curve method has been performed on synthetic and measured lidar signals. A strategy to choose a suitable range for the integration within the framework of the retrieval of optical properties is prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…The introduction of Veselovskii et al (2002) provides a good review of early attempts and the methodology. Shcherbakov (2007) and Pornsawad et al (2012) demonstrated that such methods return solely positive extinction and can produce more accurate products than the Ansmann method but use Tikhonov smoothing within the retrieval, which generates significant errors where there are substantial gradients. Though the formulation of that technique resembles that of optimal estimation, they differ in their interpretation.…”
Section: Existing Lidar Analysesmentioning
confidence: 99%
“…The introduction of Veselovskii et al (2002) provides a good review of early attempts and the methodology. Shcherbakov (2007) and Pornsawad et al (2012) demonstrated that such methods return solely positive extinction and can produce more accurate products than the Ansmann method but use Tikhonov smoothing within the retrieval, which generates significant errors where there are substantial gradients. Though the formulation of that technique resembles that of optimal estimation, they differ in their interpretation.…”
Section: Existing Lidar Analysesmentioning
confidence: 99%
“…This particle mass profiling (PMAP) polarization lidar photometer networking (POLIPHON) method can be regarded as one of the basic techniques for detailed height-resolved profiling of optical and microphysical properties of atmospheric particles. Polarization lidars equipped not only with elastic backscatter channels but also with nitrogen Raman channels increase the potential of such a monitoring site by independently measuring vertical profiles of particle backscatter and extinction coefficients (Ansmann et al, 1992;Ansmann and Müller, 2005;Shcherbakov, 2007;Samoilova and Balin, 2008;Pornsawad et al, 2012) and by providing direct observations on the relationship between backscatter and extinction (lidar ratio) for desert dust, volcanic dust, and for layers with mixtures of dust and fine-mode particles (Mattis et al, 2002Pappalardo et al, 2004;Müller et al, 2007;Wang et al, 2008;Tesche et al, 2009aTesche et al, , 2011aWiegner et al, 2011Wiegner et al, , 2012Groß et al, 2011bGroß et al, , 2012Mona et al, 2012;Papayannis et al, 2012;Sicard et al, 2012).…”
mentioning
confidence: 99%
“…Finally it is worth mentioning that, within the lidar community, other approaches rooted in the numerical derivative problem have been proved to be effective, and there are other methods providing alternative and reasonable ERes definitions (Leblanc et al, 2012;Pornsawad et al, 2012;Trickl, 2010;Shcherbakov, 2007;Eisele and Trickl, 2005;VDIVerein Deutscher Ingenieure, 1999). For this reason a more exhaustive comparison with other approaches to the evaluation of the ERes will be likely done in future in the frame of EARLINET activities.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this procedure, also known as the "step function" method, has been already tested in the frame of the first EAR-LINET algorithm intercomparison . There are alternative approaches to estimate the ERes such as the analysis of the smoothing effect on the full width at half maximum (FWHM) of a finite impulse (Leblanc et al, 2012), the response to a Heaviside step function (VDIVerein Deutscher Ingenieure, 1999; Eisele and Trickl, 2005;Vogelmann andTrickl, 2008, Trickl, 2010), or the application of the regularization theory to lidar data processing (Pornsawad et al, 2012;Shcherbakov, 2007). However, for SG filters, the "step function" method apparently shows some ambiguous results as can be seen in the examples reported in Fig.…”
Section: The Effective Resolution: the Rayleigh Criterionmentioning
confidence: 99%
See 1 more Smart Citation